Complications of rabbit anti-thymocyte globulin induction immunosuppression in HIV-infected kidney transplant recipients - Al Jurdi, Ayman; Liu, Esther C.; Salinas, Thalia; Aull, Meredith J.; Lubetzky, Michelle; Drelick, Alexander L.; Small, Catherine B.; Kapur, Sandip; Hartono, Choli; Muthukumar, Thangamani (Frontiers in Nephrology, 2022)
Background: Kidney transplantation in HIV-infected individuals with end-stage kidney disease is associated with improved survival compared to dialysis. Rabbit anti-thymocyte globulin (rATG) induction in HIV-infected kidney transplant recipients has been associated with a lower risk of acute rejection, but data on the rates of de novo malignancy and BK viremia in these patients is lacking. Methods: We performed a single-center retrospective cohort study of adult HIV-infected individuals who underwent kidney transplantation with rATG induction between January 2006 and December 2016. The primary outcome was the development of de novo malignancy. Secondary outcomes included the development of BK viremia, infections requiring hospitalization, HIV progression, biopsy-proven acute rejection, and patient and allograft survival. Results: Twenty-seven HIV-infected individuals with end-stage kidney disease received deceased (n=23) or living (n=4) donor kidney transplants. The cumulative rate of malignancy at five years was 29%, of whom 29% died because of advanced malignancy. BK viremia was detected in six participants (22%), of whom one had biopsy-proven BK virus-associated nephropathy and all of whom cleared the BK viremia. Five-year acute rejection rates, patient survival and death-censored allograft survival were 17%, 85% and 80% respectively. Conclusion: rATG induction in HIV-infected kidney transplant recipients was associated with a low risk of acute rejection, but a potentially higher risk of de novo malignancies and BK viremia in this cohort. Screening strategies to closely monitor for BK virus infection and malignancy post-transplantation may improve outcomes in HIV-infected kidney transplant recipients receiving rATG induction.